Dilated Cardiomyopathy in Paediatric Population: A Review (Cardiovascular Journal, 2019)
Dilated cardiomyopathy (DCM) is a common cardiac diagnosis in children that may result as a consequence of diverse genetic and environmental insults. The differential diagnosis remains quite broad and as a result the approach to diagnosis and management may, at times, be quite difficult. A rigorous work-up can exclude alternative causes of left ventricular (LV) dilation and dysfunction, identify etiologies that may respond to specific treatments, and guide family screening. Assessment of myocardial detection of pre-clinical DCM could significantly reduce morbidity and mortality by allowing early instigation of cardio protective therapy. This review article discusses genetic and acquired causes of DCM, diagnostic modalities and therapeutic implications in the hope of informing physicians of a clinical entity that afflicts a substantial number of children worldwide.Cardiovasc. j. 2019; 12(1): 64-74